2008
DOI: 10.1089/jpm.2007.2480
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Oncologists' Approaches to End-of-Life Care

Abstract: Purpose: To understand how oncologists provide care at the end of life, the emotions they experience in the provision of this care, and how caring for dying patients may impact job satisfaction and burnout.Participants and methods: A face-to-face survey and in-depth semistructured interview of 18 academic oncologists who were asked to describe the most recent inpatient death on the medical oncology service. Physicians were asked to describe the details of the patient death, their involvement with the care of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 17 publications
2
93
0
1
Order By: Relevance
“…Other potential models include the "solo practice model," in which oncologists assume all care from diagnosis to death, and the "congress practice model," referring to multiple consultants who specialize in various symptom and psychosocial concerns [15,34]. The solo practice model is limited by time constraints, variable interest in and comfort with discussing palliative and end-of-life care [35][36][37], and the lack of specialized training in palliative medicine [16]. This model also risks higher rates of burnout among oncologists, especially those who identify their role as rooted mainly in the biomedical realm [35].The congress model has the disadvantage of necessitating the coordination of a myriad of appointments I think she's finding that she's able to talk and express herself and that people are interested in how she's thinking and feeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential models include the "solo practice model," in which oncologists assume all care from diagnosis to death, and the "congress practice model," referring to multiple consultants who specialize in various symptom and psychosocial concerns [15,34]. The solo practice model is limited by time constraints, variable interest in and comfort with discussing palliative and end-of-life care [35][36][37], and the lack of specialized training in palliative medicine [16]. This model also risks higher rates of burnout among oncologists, especially those who identify their role as rooted mainly in the biomedical realm [35].The congress model has the disadvantage of necessitating the coordination of a myriad of appointments I think she's finding that she's able to talk and express herself and that people are interested in how she's thinking and feeling.…”
Section: Discussionmentioning
confidence: 99%
“…The solo practice model is limited by time constraints, variable interest in and comfort with discussing palliative and end-of-life care [35][36][37], and the lack of specialized training in palliative medicine [16]. This model also risks higher rates of burnout among oncologists, especially those who identify their role as rooted mainly in the biomedical realm [35].The congress model has the disadvantage of necessitating the coordination of a myriad of appointments I think she's finding that she's able to talk and express herself and that people are interested in how she's thinking and feeling. C-580i Medical relationship I think it's important that they understand from a medical point of view what's going on in my life.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that social support significantly explains job satisfaction [21,22] and positively correlates with physicians’ organizational commitment and engagement [23]. There is also some evidence showing connections between social support and learning or professional development; there are correlations between social support and physicians’ work orientation [24], as well as general practitioners’ work practices [25]. There is some evidence that social support can develop working skills in patient–caregiver relationships [13], and social support can impact managerial learning [26].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the attitudes among oncologists toward EOL care [8,9]. Jackson et al conducted a qualitative study of 18 academic oncologists and reported that oncologists varied in their approaches to EOL care [8].…”
Section: Introductionmentioning
confidence: 99%
“…Jackson et al conducted a qualitative study of 18 academic oncologists and reported that oncologists varied in their approaches to EOL care [8]. In an accompanying editorial, von Gunten expanded on this concept and labeled the oncologists as either type I or type II.…”
Section: Introductionmentioning
confidence: 99%